Chromosome-level reference genome assembly for the mountain hare (Lepus timidus) - Fekete, Zsófia; Absolon, Dominic E.; Michell, Craig; Wood, Jonathan M. D.; Goffart, Steffi; Pohjoismäki, Jaakko L. O. (Peer Community Journal)

(untitled)
We present here a high-quality genome assembly of a male mountain hare (Lepus timidus Linnaeus), from Ilomantsi, Eastern Finland, utilizing an isolated fibroblast cell line as the source for high quality DNA and RNA. Following the previously published brown hare reference genome assembly, the mountain hare is the second Finnish pilot species for the European Reference Genome Atlas (ERGA) initiative, a collaborative effort to generate reference genomes for European biodiversity. The genome was assembled using 21× PacBio HiFi sequencing data and scaffolded using the Hi-C chromosome structure capture approach. After manual curation, the primary assembly length was 2,695,305,354 bp with N50 125,755,317 bp. The largest scaffold was 181 Mbp and the scaffold N50 127 Mbp, contributing to a primary assembly consisting of 85 scaffolds and an alternate assembly with 109 scaffolds. The scaffolds include 23 autosomes, numbered according to their size, as well as X and Y chromosomes, matching the known karyotype. Telomeric regions were present on at least one end of 19 of the chromosomes. The genome has a high degree of completeness based on the BUSCO score (mammalia_odb10 database), Complete: 95.1 % [Single copy: 92.3 %, Duplicated: 2.7 %], Fragmented 0.8 %, and Missing 4.1 %. The mitochondrial genome of the cell line was sequenced and assembled separately. The assembly meets the Earth BioGenome Project criteria for a reference-standard genome assembly. Compared to the previous pseudo-reference genome assembly of  L. timidus ssp. hibernicus Bell, assembled using the rabbit genome, this new reference genome represents the nominate subspecies and the species-specific chromosomal conformation. The published genome assembly will provide a solid foundation for future genomic research on Lagomorpha, including the insights into the genomic basis of adaptations to snowy and cold environments. Furthermore, it opens opportunities for experimental analysis of mountain hare gene functions.